PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. HAZARA CIPTA PESONA - Nunu Nurjaya (GoAcademica Research dan Publishing, 2021)
Human Resources (HR) quality is one of the essential factors in improving a company's performance. Therefore we need human resources which have high competence because they can support the improvement of employee performance. This research uses a qualitative method with a descriptive analysis approach. The data used in this research is cross-section data obtained from primary data sources. In this study, the population is all employees of PT. Hazara Cipta Pesona as many as 88 employees. The sampling technique used is saturated sampling or census. The analysis used in this research is an inferential analysis using multiple linear regression. From this research, it is known that: (1) Work discipline variable has a positive and significant effect on the employee performance of PT. Hazara Cipta Pesona. (2) Work environment variables have a positive and significant impact on the performance of employees of PT. Hazara Cipta Pesona; (3) Work motivation variable has a positive and significant effect on employee performance at PT. Hazara Cipta Pesona.